A quasi-spherical red phosphor and preparation method thereof

A two-stage sintering process with controlled particle size and reducing atmosphere produces quasi-spherical red phosphors, addressing uneven distribution issues and enhancing thermal stability, thus improving yield and luminous efficiency.

CN118496854BActive Publication Date: 2024-12-13JIANGMEN KANHOO IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410380850.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-31
Publication Date
2024-12-13
Estimated Expiration
2044-03-31

AI Technical Summary

Technical Problem

The block-like crystal morphology of silicon-aluminum-based red phosphors leads to uneven distribution and reduced yield when mixed with spherical aluminate yellow-green phosphors, affecting luminous efficiency and consistency in applications.

Method used

A method involving two-stage sintering with controlled particle size and sphericity, using a reducing atmosphere to produce quasi-spherical red phosphors with improved Eu 2+ reduction, and optionally coating with silica sol to enhance thermal stability.

Benefits of technology

The method achieves even mixing with aluminate yellow-green phosphors, improving yield and luminous efficiency by controlling crystal morphology and thermal stability of red phosphors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118496854B_ABST
    Figure CN118496854B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of phosphor preparation, and discloses a quasi-spherical red phosphor, wherein the quasi-spherical red phosphor is obtained by sintering raw material powder with a particle size of less than 2 μm and a spherical crystal morphology twice under a reducing atmosphere, wherein the second sintering is a mixing of a sintered material obtained by the first sintering and the raw material powder at a mass ratio of 1:4-8 and then a second sintering. The present invention obtains a sintered material with a smaller crystal particle size by sintering part of the raw material for the first time, and mixes the sintered material obtained by the first sintering with the remaining raw material powder in proportion for the second sintering, and controls the process of the second sintering so that the particles of the raw material can adhere to and grow on the surface of small grains during the second sintering process to form large grains to produce an effect similar to overmolding, thereby improving the sphericity of the red phosphor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of phosphor preparation, and in particular to a quasi-spherical red phosphor and a preparation method thereof. Background Art

[0002] At present, the commercial phosphors with peak wavelengths between 600 and 680 nm are mainly Ca (1-x) Sr x AlSiN3:Eu 2+ The crystal morphology of the silicon-aluminum-based red phosphor of the 1113 system is generally block-like; since the chemical stability of the 1113 system red phosphor is better than that of the 258 system red phosphor of the similar wavelength, Ca is generally selected in the application end. (1-x) Sr x AlSiN3:Eu 2+ The system's red phosphor and aluminate yellow-green phosphor are combined and packaged, and white light is stimulated by the blue light chip.

[0003] Prior art 1: Chinese patent 201410630341.7 discloses a red luminescent phosphor and a preparation method thereof. The chemical formula of the red luminescent phosphor is M 1-x A y Al 2-y SiN4:xEu; wherein M is at least one of Mg, Ca, Sr, Ba, Y and Sc, A is at least one of Gd and Ga, and 0.01≤x≤0.2, 0≤y≤1. The preparation method of the red luminescent phosphor comprises the following steps: a. 1-x A y Al 2-y The raw materials M, A, Al, Si and Eu are weighed in the stoichiometric ratio of each element in SiN4:xEu, and the weighed raw materials are placed in an arc melting furnace for smelting to form an alloy; b. The alloy obtained in step a is crushed and ball-milled, and then sintered at a high temperature under a protective atmosphere. After cooling, the alloy is taken out, washed and dried to obtain a red luminescent phosphor; the preparation cost of the red luminescent phosphor in the present invention is low, and the preparation process is simple and easy to control.

[0004] The technical solution of the above patent obtains red luminescent phosphor by high temperature solid phase sintering, Ca (1-x) Sr x AlSiN3:Eu 2+ The silicon-aluminum-based red phosphor of the system is generally obtained by high-temperature solid-phase sintering.

[0005] However, the surface of the block-like crystal has a large reflectivity to light, and the crystal morphology of the aluminate yellow-green phosphor used in combination with it is spherical. When these two phosphors are mixed in the packaging glue, the spherical aluminate yellow-green phosphor tends to settle quickly while the block-like phosphor settles slowly, resulting in uneven local distribution ratios during packaging glue dispensing, which in turn causes inconsistent ratios of the two phosphors in different chips, affecting the yield and luminous efficiency at the application end.

[0006] Therefore, it is necessary to find a preparation method that can prepare spherical red phosphors so that the prepared red phosphors have more advantages in application. Summary of the invention

[0007] One of the purposes of the present invention is to provide a quasi-spherical red phosphor to solve the problem that the silicon-aluminum-based red phosphor crystal morphology prepared by the prior art is generally block-like, resulting in low yield at the application end. The quasi-spherical red phosphor crystal morphology of the present invention is quasi-spherical, and the activator is fully reduced, with extremely high luminescence performance and thermal stability. At the application end, it can also be evenly mixed with the aluminate yellow-green phosphor used in combination therewith to improve the yield.

[0008] Another object of the present invention is to provide a method for preparing a quasi-spherical red phosphor, by controlling the ratio of small-size crystals to large-size crystals, and improving the sphericity of the red phosphor through secondary sintering, while also fully reducing the Eu 3+ Reduction of Eu 2+ , improve the market competitiveness of products.

[0009] To achieve the above object, the present invention provides a quasi-spherical red phosphor, the chemical formula of which is E 1-x D y Q z N3:xEu 2+ , the E element is at least one of Mg, Ca, Sr, and Ba, the D element is at least one of Al and Ga, the Q element is at least one of Si and Ge, 0.001≤x≤0.1; 0.5≤y≤2; 0.5≤z≤2;

[0010] The quasi-spherical red phosphor is obtained by sintering a raw material powder with a particle size of less than 2 μm and a spherical crystal morphology twice in a reducing atmosphere, wherein the second sintering is performed by mixing the sintered material obtained by the first sintering with the raw material powder in a mass ratio of 1:4-8 and then performing the second sintering; wherein the crystal particle size of the sintered material obtained by the first sintering is smaller than the crystal particle size formed by the growth of the raw material powder in the second sintering.

[0011] The invention divides the raw material powder into two parts, firstly performs the first sintering of one part in a reducing atmosphere to obtain a sintered material, and then mixes the sintered material with the remaining raw material powder and performs the second sintering in a reducing atmosphere.

[0012] In the technical scheme of the present invention, the present invention controls the sintering temperature and sintering pressure of the first sintering to be lower than those of the second sintering, so that the crystal particle size of the sintered material obtained by the first sintering is smaller than the crystal particle size of the second sintering. Since the small grains of the first sintering have been formed, the particles of the raw material will adhere and grow on the surface of the small grains during the second sintering process to form large grains. Therefore, the ratio of the sintered material obtained by the first sintering and the new raw material powder in the second sintering process is particularly important. Too little or too much raw material powder will affect the uniformity of the raw material and the effect of the raw material particles on the attachment and growth of the small grain surface, thereby affecting the sphericity and luminescence performance of the product.

[0013] Preferably, the crystal particle size D50 of the sintered material obtained by the first sintering is 3-5 μm; during the second sintering process, the raw material particles grow on the crystals of the sintered material obtained by the first sintering, forming an effect similar to overmolding, thereby improving the sphericity of the product.

[0014] Furthermore, the mass ratio of the sintered material obtained by the first sintering to the raw material powder can be selected to be 1:4, 1:4.5, 1:5, 1:5.5, 1:6, 1:6.5, 1:7, 1:7.5, 1:8.

[0015] In order to improve the sphericity of the final red phosphor, the problem of uneven mixing caused by differences in crystal form and particle size of the raw materials of various elements can be avoided by controlling the particle size of the raw material powder, so that the sphericity of crystal growth during sintering is improved. Preferably, the raw material powder is a powder with a particle size of less than 2μm and a spherical crystal morphology.

[0016] The present invention also provides a method for preparing a spherical red phosphor, comprising the following steps:

[0017] Step 1: The chemical formula of the spherical red phosphor is E 1-x D y Q z N3:xEu 2+ , the E element is at least one of Mg, Ca, Sr, and Ba, the D element is Al or / and Ga, the Q element is Si or / and Ge, 0.001≤x≤0.1; 0.5≤y≤2; 0.5≤z≤2, and the raw material powder is weighed according to the above general formula;

[0018] Step 2: Divide the raw material powder into a first powder and a second powder in a mass ratio of 1:4-8, and perform a first sintering on the first powder in a weak reducing atmosphere of a mixture of H2 and N2 to obtain a primary sintered material, wherein the sintering temperature of the first sintering is 1000-2000°C, the pressure is 0.5-2.0MPa, and the insulation time is 5-20h, and the volume proportion of H2 in the weak reducing atmosphere of a mixture of H2 and N2 is 0.1%-3%;

[0019] Step 3: The primary sintered material obtained in step 2 is subjected to collision dispersion and then mixed with the second powder, and a second sintering is performed in a weak reducing atmosphere of a mixture of H2 and N2 to obtain a secondary sintered material, wherein the sintering temperature of the second sintering is 1500-2500°C, the pressure is 1.0-5.0MPa, and the insulation time is 5-20h, and the volume proportion of H2 in the weak reducing atmosphere of a mixture of H2 and N2 is 4%-10%;

[0020] Step 4: subjecting the secondary sintered material obtained in step 3 to collision dispersion, ball milling, and washing in sequence to obtain the quasi-spherical red phosphor;

[0021] The sintering temperature and sintering pressure of the first sintering in step 2 must be lower than the sintering temperature and sintering pressure of the second sintering in step 3.

[0022] In the method for preparing the quasi-spherical red phosphor of the present invention, the step 3 uses collision dispersion to disperse the primary sintered material obtained in step 2 into particles, thereby reducing the damage of external forces to the crystal form of the powder and avoiding the problem of reduced product performance.

[0023] Preferably, the sintering temperature of the first sintering in step 2 may be selected from 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, 1500°C, 1600°C, 1700°C, 1800°C, 1900°C, and 2000°C.

[0024] Preferably, the sintering pressure of the first sintering in step 2 can be selected from 0.5 MPa, 0.6 MPa, 0.7 MPa, 0.8 MPa, 0.9 MPa, 1.0 MPa, 1.1 MPa, 1.2 MPa, 1.3 MPa, 1.4 MPa, 1.5 MPa, 1.6 MPa, 1.7 MPa, 1.8 MPa, 1.9 MPa, and 2.0 MPa.

[0025] Preferably, the holding time for the first sintering in step 2 can be selected to be 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, or 20h.

[0026] Preferably, the sintering temperature of the second sintering in step 3 can be selected from 1500°C, 1600°C, 1700°C, 1800°C, 1900°C, 2000°C, 2100°C, 2200°C, 2300°C, 2400°C, and 2500°C.

[0027] Preferably, the sintering pressure of the second sintering in step 3 can be selected from 1.0 MPa, 1.3 MPa, 1.5 MPa, 1.7 MPa, 2.0 MPa, 2.3 MPa, 2.5 MPa, 2.7 MPa, 3.0 MPa, 3.3 MPa, 3.5 MPa, 3.7 MPa, 4.0 MPa, 4.3 MPa, 4.5 MPa, 4.7 MPa, and 5.0 MPa.

[0028] Preferably, the holding time for the second sintering in step 3 can be selected as 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, or 20h.

[0029] Furthermore, the raw material powder is a spherical powder with a particle size of less than 2 μm, which is prepared by the following steps:

[0030] The raw material is placed in a ball mill, zirconium beads with a diameter of 0.5-2 cm and a weight of 1-5 times the weight of the raw material are added, ball milling is performed for 1-10 hours, and the raw material powder is obtained by sieving.

[0031] Furthermore, the specific operation of step 4 is: putting the secondary sintered material obtained in step 3 into a crushing tank, placing it on a ball mill for powder block collision dispersion, and sieving the powder until there are no obvious particles. Then, the powder is put into a ball mill, and zirconium beads with a diameter of 0.5-2 cm and a weight of 1-5 times the weight of the powder and deionized water with a volume of 0.1-3 times the weight of the powder are added for ball milling for 0.5-5h, and then washed with deionized water until the conductivity is less than 10μs / cm.

[0032] Preferably, the particle size D50 of the spherical red phosphor obtained in step 4 is 15-25 μm.

[0033] Preferably, the preparation method of the quasi-spherical red phosphor of the present invention also includes step 5: under heating in a constant temperature water bath at a temperature of 50-90°C, placing the quasi-spherical red phosphor obtained in step 4 in an ethanol solution diluted at a ratio of deionized water to ethanol = 1:1 and stirring, adding a corresponding volume of silica sol at a ratio of 0.1% to 10% of the mass of the powder, ultrasonically stirring for 1-5 hours, filtering and drying to obtain the quasi-spherical red phosphor coated with silica sol.

[0034] The present invention can effectively improve the thermal stability of the red fluorescent powder by coating a silica sol coating layer on the surface of the spherical red fluorescent powder.

[0035] Furthermore, the preparation method of the spherical red phosphor of the present invention also includes step 6: adding the spherical red phosphor obtained in step 5 to an ethanol solution under heating in a constant temperature water bath at a temperature of 50-90°C, adding a corresponding volume of silica sol at a rate of 0.1%-10% of the mass of the powder for secondary coating, ultrasonically stirring for 1-5 hours, filtering and drying to obtain a double-layer silica sol-coated spherical red phosphor.

[0036] By using the silica sol multiple coating process, a coating layer is applied on the powder surface without affecting the luminescence performance of the powder to improve the thermal stability of the powder.

[0037] Beneficial Effects

[0038] Compared with the prior art, the present invention has at least the following advantages:

[0039] (1) The present invention performs a first sintering of part of the raw materials to obtain a sintered material with a smaller crystal particle size, and mixes the sintered material obtained by the first sintering with the remaining raw material powder in proportion to perform a second sintering, and controls the process of the second sintering so that during the second sintering process, the particles of the raw materials will adhere to and grow on the surface of the small grains to form large grains to produce an effect similar to overmolding, thereby improving the sphericity of the red phosphor;

[0040] (2) The present invention controls the mass ratio of the sintering material of the first sintering to the remaining raw material powder to ensure that the raw material powder can surround and adhere to the surface of the grains of the sintering material of the first sintering, thereby avoiding that the unreasonable ratio of the raw material powder to the sintering material of the first sintering affects the uniformity and adhesion of the raw materials, thereby affecting the sphericity of the product obtained by the second sintering;

[0041] (3) The present invention performs secondary sintering in a reducing atmosphere so that the Eu activator in the prepared spherical red phosphor can be fully reduced to Eu 2+ , effectively improve the luminescence performance and thermal stability of phosphors;

[0042] (4) The present invention controls the reducing gas content of the reducing atmosphere during the first sintering and the second sintering, thereby fully reducing the Eu activator so that Eu 3+ Faster and more thorough restoration to Eu 2+ , effectively improving the luminous performance and thermal stability of the product. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] The present invention is further described below in conjunction with the accompanying drawings and embodiments;

[0044] Figure 1 is a crystal morphology diagram of Example 1 of the present invention;

[0045] Figure 2 is a crystal morphology diagram of Example 4 of the present invention;

[0046] Figure 3 is a crystal morphology diagram of Example 5 of the present invention;

[0047] Figure 4 is a crystal morphology diagram of Comparative Example 1 of the present invention;

[0048] Figure 5 is a crystal morphology diagram of Comparative Example 2 of the present invention;

[0049] Figure 6 is a crystal morphology diagram of Comparative Example 5 of the present invention;

[0050] Figure 7 is a crystal morphology diagram of Comparative Example 6 of the present invention;

[0051] Figure 8 It is the crystal morphology picture of comparative example 7 of the present invention. DETAILED DESCRIPTION

[0052] The present invention will be further described below in conjunction with the embodiments, but it does not constitute any limitation to the present invention. Any limited number of modifications made within the scope of the claims of the present invention are still within the scope of the claims of the present invention.

[0053] In order to explain the technical content of the present invention in detail, further description is given below in conjunction with the implementation modes.

[0054] In the following examples and comparative examples, silica sol was purchased from Jiangmen Huihe Silicon Products Co., Ltd., and its concentration was 30%;

[0055] In the following examples and comparative examples, the ball mill rotation speed for powder block collision dispersion is 100 rpm.

[0056] Example 1

[0057] A spherical red phosphor is prepared by the following steps:

[0058] Step 1: weigh 166.8 g of strontium nitride, 9.9 g of calcium nitride, 82.0 g of aluminum nitride, 93.5 g of silicon nitride, and 14.1 g of europium oxide as raw materials, respectively place them in a ball mill, add zirconium beads with a diameter of 1 cm and a weight three times the weight of the raw materials, ball mill for 5 hours, sieve to obtain strontium nitride, calcium nitride, aluminum nitride, silicon nitride, and europium oxide powders with a particle size of <2 μm, and mix all the powders to obtain raw material powder;

[0059] Step 2: The raw material powder is divided into a first powder and a second powder at a mass ratio of 1:6, and the first powder is subjected to a first sintering in a weak reducing atmosphere of a mixture of H2 and N2 to obtain a primary sintered material, wherein the sintering temperature of the first sintering is 1600° C., the pressure is 0.8 MPa, and the holding time is 6 h. The volume proportion of H2 in the weak reducing atmosphere of a mixture of H2 and N2 is 2%;

[0060] Step 3: The primary sintered material obtained in step 2 is put into a crushing tank, and placed on a ball mill for powder block collision dispersion. After the powder is dispersed until there are no obvious particles, the sintered powder with a particle size D50 of 4 μm is sieved and mixed with the second powder, and a second sintering is performed in a weak reducing atmosphere mixed with H2 and N2 to obtain a secondary sintered material, wherein the sintering temperature of the second sintering is 1800°C, the pressure is 1.5 MPa, and the insulation time is 10 h. The volume proportion of H2 in the weak reducing atmosphere mixed with H2 and N2 is 5%;

[0061] Step 4: Put the secondary sintered material obtained in step 3 into a crushing tank, place it on a ball mill for powder block collision dispersion, wait until the powder is dispersed without obvious particles, sieve to obtain the powder, then put the powder into a ball mill, add zirconium beads with a diameter of 0.8 cm and a weight of 1.5 times the weight of the powder and deionized water with a volume of 0.8 times the weight of the powder, ball mill for 1.5 hours, take it out, wash it with deionized water until the conductivity is less than 10μs / cm, dry and sieve to obtain the spherical red phosphor.

[0062] Example 2

[0063] It is generally the same as Example 1, except that:

[0064] The step 1 is changed to: weigh 184.2 g of strontium nitride, 4.4 g of calcium nitride, 82.0 g of aluminum nitride, 93.5 g of silicon nitride, and 1.8 g of europium oxide as raw materials, respectively place them in a ball mill, add zirconium beads with a diameter of 1 cm and a weight three times the weight of the raw materials, ball mill for 5 hours, sieve to obtain strontium nitride, calcium nitride, aluminum nitride, silicon nitride, and europium oxide powders with a particle size of less than 2 μm, and mix all the powders to obtain the raw material powder.

[0065] Example 3

[0066] It is generally the same as Example 1, except that:

[0067] The step 1 is changed to: weigh 125.9 g of calcium nitride, 106.6 g of aluminum nitride, 121.6 g of silicon nitride, and 9.2 g of europium oxide as raw materials, respectively place them in a ball mill, add zirconium beads with a diameter of 1 cm and a weight three times the weight of the raw materials, ball mill for 5 hours, sieve to obtain calcium nitride, aluminum nitride, silicon nitride, and europium oxide powders with a particle size of less than 2 μm, and mix all the powders to obtain the raw material powder.

[0068] Example 4

[0069] It is generally the same as Example 1, except that:

[0070] The mass ratio of the first powder to the second powder in step 2 is 1:4.

[0071] Example 5

[0072] It is generally the same as Example 1, except that:

[0073] The mass ratio of the first powder to the second powder in step 2 is 1:8.

[0074] Example 6

[0075] A spherical red phosphor is prepared by the following steps:

[0076] Step 1: weigh 166.8 g of strontium nitride, 9.9 g of calcium nitride, 82.0 g of aluminum nitride, 93.5 g of silicon nitride, and 14.1 g of europium oxide as raw materials, respectively place them in a ball mill, add zirconium beads with a diameter of 1 cm and a weight three times the weight of the raw materials, ball mill for 5 hours, sieve to obtain strontium nitride, calcium nitride, aluminum nitride, silicon nitride, and europium oxide powders with a particle size of <2 μm, and mix all the powders to obtain raw material powder;

[0077] Step 2: The raw material powder is divided into a first powder and a second powder at a mass ratio of 1:6, and the first powder is subjected to a first sintering in a weak reducing atmosphere of a mixture of H2 and N2 to obtain a primary sintered material, wherein the sintering temperature of the first sintering is 1600° C., the pressure is 0.8 MPa, and the holding time is 6 h. The volume proportion of H2 in the weak reducing atmosphere of a mixture of H2 and N2 is 2%;

[0078] Step 3: The primary sintered material obtained in step 2 is put into a crushing tank, and placed on a ball mill for powder block collision dispersion. After the powder is dispersed until there are no obvious particles, the sintered powder with a particle size D50 of 4 μm is sieved and mixed with the second powder, and a second sintering is performed in a weak reducing atmosphere mixed with H2 and N2 to obtain a secondary sintered material, wherein the sintering temperature of the second sintering is 1800°C, the pressure is 1.5 MPa, and the insulation time is 10 h. The volume proportion of H2 in the weak reducing atmosphere mixed with H2 and N2 is 5%;

[0079] Step 4: Put the secondary sintered material obtained in step 3 into a crushing tank, place it on a ball mill for powder block collision dispersion, wait until the powder is dispersed without obvious particles, sieve to obtain the powder, then put the powder into a ball mill, add zirconium beads with a diameter of 0.8 cm and a weight of 1.5 times the weight of the powder and deionized water with a volume of 0.8 times the weight of the powder, ball mill for 1.5 hours, take it out, wash it with deionized water until the conductivity is less than 10μs / cm, dry and sieve to obtain the spherical red phosphor.

[0080] Step 5: While heating in a constant temperature water bath at 85°C, place the spherical red phosphor obtained in step 4 in an ethanol solution diluted at a ratio of deionized water to ethanol = 1:1 and stir, add 5% silica sol by volume based on the mass of the powder, ultrasonically stir for 3 hours, filter and dry to obtain the silica sol-coated spherical red phosphor.

[0081] Example 7

[0082] A spherical red phosphor is prepared by the following steps:

[0083] Step 1: weigh 166.8 g of strontium nitride, 9.9 g of calcium nitride, 82.0 g of aluminum nitride, 93.5 g of silicon nitride, and 14.1 g of europium oxide as raw materials, respectively place them in a ball mill, add zirconium beads with a diameter of 1 cm and a weight three times the weight of the raw materials, ball mill for 5 hours, sieve to obtain strontium nitride, calcium nitride, aluminum nitride, silicon nitride, and europium oxide powders with a particle size of <2 μm, and mix all the powders to obtain raw material powder;

[0084] Step 2: The raw material powder is divided into a first powder and a second powder at a mass ratio of 1:6, and the first powder is subjected to a first sintering in a weak reducing atmosphere of a mixture of H2 and N2 to obtain a primary sintered material, wherein the sintering temperature of the first sintering is 1600° C., the pressure is 0.8 MPa, and the holding time is 6 h. The volume proportion of H2 in the weak reducing atmosphere of a mixture of H2 and N2 is 2%;

[0085] Step 3: The primary sintered material obtained in step 2 is put into a crushing tank, and placed on a ball mill for powder block collision dispersion. After the powder is dispersed until there are no obvious particles, the sintered powder with a particle size D50 of 4 μm is sieved and mixed with the second powder, and a second sintering is performed in a weak reducing atmosphere mixed with H2 and N2 to obtain a secondary sintered material, wherein the sintering temperature of the second sintering is 1800°C, the pressure is 1.5 MPa, and the insulation time is 10 h. The volume proportion of H2 in the weak reducing atmosphere mixed with H2 and N2 is 5%;

[0086] Step 4: Put the secondary sintered material obtained in step 3 into a crushing tank, place it on a ball mill for powder block collision dispersion, wait until the powder is dispersed without obvious particles, sieve to obtain the powder, then put the powder into a ball mill, add zirconium beads with a diameter of 0.8 cm and a weight of 1.5 times the weight of the powder and deionized water with a volume of 0.8 times the weight of the powder, ball mill for 1.5 hours, take it out, wash it with deionized water until the conductivity is less than 10μs / cm, dry and sieve to obtain the spherical red phosphor.

[0087] Step 5: While heating in a constant temperature water bath at 85°C, place the spherical red phosphor obtained in step 4 in an ethanol solution diluted at a ratio of deionized water to ethanol = 1:1 and stir, add 5% silica sol by volume based on the mass of the powder, ultrasonically stir for 3 hours, filter and dry to obtain the silica sol-coated spherical red phosphor.

[0088] Step 6: Under heating in a constant temperature water bath at 85°C, add the spherical red phosphor obtained in step 5 to an ethanol solution diluted at a ratio of deionized water to ethanol = 1:1, add 5% silica sol by volume based on the mass of the powder for secondary coating, ultrasonically stir for 3 hours, filter and dry to obtain a double-layer silica sol-coated spherical red phosphor.

[0089] Example 8

[0090] It is generally the same as Example 1, except that:

[0091] The step 1 is changed to: weigh 252.3 g of barium nitride, 9.9 g of calcium nitride, 82.0 g of aluminum nitride, 93.5 g of silicon nitride, and 14.1 g of europium oxide as raw materials, respectively place them in a ball mill, add zirconium beads with a diameter of 1 cm and a weight three times the weight of the raw materials, ball mill for 5 hours, sieve to obtain strontium nitride, calcium nitride, aluminum nitride, silicon nitride, and europium oxide powders with a particle size of less than 2 μm, and mix all the powders to obtain the raw material powder.

[0092] Comparative Example 1

[0093] It is generally the same as Example 1, except that:

[0094] The step 2 is changed to: dividing the raw material powder into a first powder and a second powder in a mass ratio of 1:6, and sintering the first powder for the first time in a weak reducing atmosphere of a mixture of H2 and N2 to obtain a primary sintered material, wherein the sintering temperature of the first sintering is 1800°C, the pressure is 1.5MPa, and the insulation time is 10h, and the volume proportion of H2 in the weak reducing atmosphere of a mixture of H2 and N2 is 5%.

[0095] Comparative Example 2

[0096] It is generally the same as Example 1, except that:

[0097] The step 2 is changed to: dividing the raw material powder into a first powder and a second powder at a mass ratio of 1:6, and performing a first sintering on the first powder in a weak reducing atmosphere of a mixture of H2 and N2 to obtain a primary sintered material, wherein the sintering temperature of the first sintering is 1800° C., the pressure is 1.5 MPa, the holding time is 10 h, and the volume proportion of H2 in the weak reducing atmosphere of a mixture of H2 and N2 is 5%;

[0098] The step 3 is changed to: putting the primary sintered material obtained in step 2 into a crushing tank, placing it on a ball mill for powder block collision dispersion, and after the powder is dispersed until there are no obvious particles, sieving to obtain sintered powder with a particle size D50 of 4 μm, mixing it with the second powder, and performing a second sintering in a weak reducing atmosphere of a mixture of H2 and N2 to obtain a secondary sintered material, wherein the sintering temperature of the second sintering is 1600°C, the pressure is 0.6 MPa, and the insulation time is 6 hours, and the volume proportion of H2 in the weak reducing atmosphere of a mixture of H2 and N2 is 2%.

[0099] Comparative Example 3

[0100] It is generally the same as Example 1, except that:

[0101] The step 2 is changed to: dividing the raw material powder into a first powder and a second powder at a mass ratio of 1:6, and sintering the first powder for the first time in a pure N2 atmosphere to obtain a primary sintered material, wherein the sintering temperature of the first sintering is 1600°C, the pressure is 0.8MPa, and the insulation time is 6h.

[0102] Comparative Example 4

[0103] It is generally the same as Example 1, except that:

[0104] The step 3 is changed to: putting the primary sintered material obtained in step 2 into a crushing tank, placing it on a ball mill for powder block collision dispersion, and after the powder is dispersed until there are no obvious particles, sieving to obtain sintered powder with a particle size D50 of 4 μm, mixing it with the second powder, and performing a second sintering in a weak reducing atmosphere of a mixture of H2 and N2 to obtain a secondary sintered material, wherein the sintering temperature of the second sintering is 1800°C, the pressure is 1.5 MPa, the insulation time is 10 h, and the volume proportion of H2 in the weak reducing atmosphere of a mixture of H2 and N2 is 2%.

[0105] Comparative Example 5

[0106] It is generally the same as Example 1, except that:

[0107] The mass ratio of the first powder to the second powder in step 2 is 2:1.

[0108] Comparative Example 6

[0109] It is generally the same as Example 1, except that:

[0110] The step 1 is changed to: weigh 166.8 g of strontium nitride, 9.9 g of calcium nitride, 82.0 g of aluminum nitride, 93.5 g of silicon nitride, and 14.1 g of europium oxide without pretreatment, and mix them to obtain a raw material powder, wherein the particle size D50 of the raw material powder is 3-10 μm.

[0111] Comparative Example 7

[0112] It is generally the same as Example 1, except that:

[0113] The mass ratio of the first powder to the second powder in step 2 is 1:10.

[0114] Performance Testing

[0115] 1. Crystal morphology: The crystal morphology of the final products of the embodiments and comparative examples was tested using a HORIBA S-3400N scanning electron microscope.

[0116] The red phosphors obtained in Examples 1, 4, 5 and Comparative Examples 1, 2, 5, 6, and 7 were subjected to crystal morphology testing. The results are as follows: Figure 1-8 shown.

[0117] According to the crystal morphology diagrams of Example 1, Example 4 and Example 5, it can be seen that the present invention improves the sphericity of the red phosphor by controlling the ratio of the sintered material obtained in the first sintering process and the new raw material powder in the second sintering process; among them, the crystal sphericity of Example 1 is the best, indicating that the ratio of the sintered material obtained in the first sintering process and the new raw material powder in the second sintering process of the present invention is the key factor in the sphericity of the product red phosphor, and the appropriate ratio can effectively control the amount of raw material powder attached to the surface of the sintered material obtained in the first sintering, thereby controlling the crystal growth trend of the red phosphor in the secondary sintering and improving the sphericity.

[0118] The crystal morphology diagrams of Comparative Examples 5 and 7 also confirm the advantages of the solution of the present invention;

[0119] In comparative example 5, too little raw material powder was mixed with the sintered material obtained by the first sintering, and the sphericity of the crystal was greatly reduced. The possible reason is that when too little raw material powder was attached to the sintered material obtained by the first sintering, the raw material particles were not attached uniformly, resulting in poor attachment and growth of the raw material particles on the surface of the small crystal grains obtained by the first sintering, which resulted in a significant reduction in the sphericity of the final red phosphor.

[0120] In Comparative Example 7, too much raw material powder was mixed with the sintered material obtained by the first sintering, and the sphericity of the crystal was greatly reduced. The possible reason is that due to the excessive amount of raw material powder, some of the raw material powder was difficult to adhere to the surface of the small-grain sintered material obtained by the first sintering, and the uniformity of the raw material was greatly reduced. Some of the raw material powder that could not adhere to the surface of the small grains could only grow on the periphery of the small grains during the secondary sintering process and contact and adhere to the raw material powder attached to the surface of the small grains, resulting in difficulty in controlling the crystal sphericity of the red phosphor.

[0121] According to the crystal morphology diagram of Comparative Example 6, if a raw material powder that has not been pretreated is used, even if the sintering process of the present invention is adopted, the obtained red phosphor will only be in the form of strips, and because the raw material is not a raw material powder with a particle size of less than 2μm and a spherical crystal morphology, its crystal surface is relatively rough and uneven.

[0122] According to the comparison of the crystal morphology diagrams of Example 1 and Comparative Examples 1 and 2, it can be seen that the present invention controls the sintering temperature and sintering pressure of the first sintering to be lower than those of the second sintering, so that the crystal particle size of the sintered material obtained by the first sintering is smaller than the crystal particle size of the second sintering. Since the small grains of the first sintering have been formed, the particles of the raw material will adhere to and grow on the surface of the small grains during the second sintering process to form large grains; while the crystals formed by the first sintering of Comparative Examples 1 and 2 are not small grains, which makes it difficult to control the crystal growth trend of the subsequent secondary sintering, thereby causing the sphericity of the obtained red phosphor to be greatly reduced.

[0123] 2. Luminescence performance and thermal stability of phosphors: The luminescence performance data of the final products of the embodiments and comparative examples were tested using a HAAS-2000 high-precision rapid light performance test radiometer. The thermal stability performance test of the final products of the embodiments and comparative examples specifically includes the following steps: placing the sample in an aging box at 120°C and 0.1MPa for 96 hours, and comparing the data (relative brightness, spectrum and particle size data) before and after the sample test, where CIEx and CIEy refer to color coordinates.

[0124] The red phosphors obtained in Examples 1-8 and Comparative Examples 1-7 were subjected to performance tests according to the above test method. The results are shown in Tables 1 and 2.

[0125] Table 1 Test results of luminescence performance of red phosphors in Examples 1-8 and Comparative Examples 1-7

[0126]

[0127] According to the results in Table 1 and the crystal morphology diagrams of some embodiments and comparative examples, it can be seen that:

[0128] From the data comparison of Examples 1-3, it can be seen that the ratio of raw materials will affect the wavelength of the red phosphor, thereby affecting the luminescent properties of the red phosphor.

[0129] From the comparison of the data of Example 1, Example 4 and Example 5, it can be seen that since the red phosphor obtained in Example 1 has a higher sphericity, its luminescence performance is also improved to a certain extent.

[0130] From the comparison of the data of Example 1, Example 6 and Example 7, it can be seen that the coating of silica sol will not have a significant effect on the luminescent properties of the red phosphor.

[0131] Since Example 8 uses different materials, its luminous performance cannot be compared with other examples.

[0132] As can be seen from the crystal morphology diagrams of Comparative Examples 1, 2, 5, 6 and 7, the sphericity of the red phosphor has been greatly reduced, resulting in a certain degree of reduction in the luminescence performance of the red phosphor, but the impact of the reduction in the sphericity of the red phosphor mainly occurs at the application end. The purpose of improving the sphericity of the red phosphor is to enable the red phosphor and the spherical aluminate yellow-green phosphor to be evenly mixed at the application end, and there will be no obvious difference in the sedimentation speed of the two during the application process, thereby improving the yield and luminous efficiency of the application end.

[0133] According to the data comparison between Example 1 and Comparative Examples 3 and 4, since the sintering atmospheres used in Comparative Examples 3 and 4 are inconsistent with the technical solution of the present invention, Comparative Example 3 uses a pure nitrogen atmosphere during the sintering process, while Comparative Example 4 uses a weaker reducing gas atmosphere, resulting in Eu 3+ Not fully reduced to Eu 2+ , which results in a significant decrease in the luminescence performance of the red phosphor.

[0134] Table 2 Thermal stability test results of red phosphors in Examples 1, 6 and 7

[0135]

[0136] According to the results in Table 2, we can see that:

[0137] In Example 1, the data of the uncoated sample changed greatly before and after the thermal stability test, indicating that the thermal stability of the sample was poor; in Example 6, the performance data of the sample coated with a layer of silica sol changed little before and after the thermal stability test, indicating that the thermal stability of the sample was good; in Example 7, the performance data of the red phosphor coated with two layers of silica sol changed the least before and after the thermal stability test, indicating that the thermal stability of the sample was the best.

[0138] The embodiments presented herein are only embodiments selected according to the combination of all possible embodiments. The appended claims should not be limited by the embodiments describing the present invention. Some numerical ranges used in the claims include sub-ranges therein, and the changes in these ranges should also be covered by the appended claims.

Claims

1. A method for preparing a spherical red phosphor, characterized in that: The steps include: Step 1: The chemical formula of the spherical red phosphor is E 1-x D y Q z N3:xEu 2+ , the E element is at least one of Mg, Ca, Sr, and Ba, the D element is Al or / and Ga, the Q element is Si or / and Ge, 0.001≤x≤0.1; 0.5≤y<2; 0.5≤z<2, and the raw material powder is weighed according to the chemical formula, and the raw material powder is a powder with a particle size of less than 2 μm and a spherical crystal morphology; Step 2: Divide the raw material powder into a first powder and a second powder in a mass ratio of 1:4-8, and perform a first sintering on the first powder in a weak reducing atmosphere of a mixture of H2 and N2 to obtain a primary sintered material, wherein the sintering temperature of the first sintering is 1000-2000°C, the pressure is 0.5-2.0MPa, and the holding time is 5-20h, and the volume proportion of H2 in the weak reducing atmosphere of a mixture of H2 and N2 is 0.1%-3%; Step 3: The primary sintered material obtained in step 2 is subjected to collision dispersion and then mixed with the second powder, and a second sintering is performed in a weak reducing atmosphere of a mixture of H2 and N2 to obtain a secondary sintered material, wherein the sintering temperature of the second sintering is 1500-2500°C, the pressure is 1.0-5.0MPa, and the holding time is 5-20h, and the volume proportion of H2 in the weak reducing atmosphere of a mixture of H2 and N2 is 4%-10%; Step 4: subjecting the secondary sintered material obtained in step 3 to collision dispersion, ball milling, and washing in sequence to obtain the spherical red phosphor; The sintering temperature and sintering pressure of the first sintering in step 2 must be lower than the sintering temperature and sintering pressure of the second sintering in step 3.

2. The method for preparing the spherical red phosphor according to claim 1, characterized in that: The raw material powder is a powder with a particle size of less than 2 μm and a spherical crystal morphology, and is prepared by the following steps: The raw material is placed in a ball mill, zirconium beads with a diameter of 0.5-2 cm and a weight of 1-5 times the weight of the raw material are added, ball milling is performed for 1-10 hours, and the raw material powder is obtained by sieving.

3. The method for preparing the spherical red phosphor according to claim 1, characterized in that: The specific operation of step 4 is: putting the secondary sintered material obtained in step 3 into a crushing tank, placing it on a ball mill for powder block collision dispersion, and sieving the powder until there are no obvious particles. Then, the powder is put into a ball mill, and zirconium beads with a diameter of 0.5-2cm and a weight of 1-5 times the weight of the powder and deionized water with a volume of 0.1-3 times the weight of the powder are added to perform ball milling for 0.5-5h, and then washed with deionized water until the conductivity is less than 10μs / cm to obtain the spherical red phosphor.

4. The method for preparing the spherical red phosphor according to claim 1, characterized in that: The method further includes step 5: placing the spherical red phosphor obtained in step 4 in an ethanol solution diluted with deionized water and ethanol in a ratio of 1:1 and stirring the solution under heating in a constant temperature water bath at a temperature of 50-90°C, adding a corresponding volume of silica sol at a ratio of 0.1%-10% of the mass of the powder, ultrasonically stirring the solution for 1-5 hours, and filtering and drying the solution to obtain the spherical red phosphor coated with silica sol.

5. The method for preparing the spherical red phosphor according to claim 1, characterized in that: The method further includes step 6: adding the spherical red phosphor obtained in step 5 to an ethanol solution diluted with deionized water and ethanol in a ratio of 1:1 under heating in a constant temperature water bath at a temperature of 50-90°C, adding a corresponding volume of silica sol at a ratio of 0.1%-10% of the mass of the powder for secondary coating, ultrasonically stirring for 1-5 hours, filtering and drying to obtain a double-layer silica sol-coated spherical red phosphor.